Permafrost Stores a Globally Significant Amount of Mercury. Issue 3 (5th February 2018) - Schuster, Paul F.; Schaefer, Kevin M.; Aiken, George R.; Antweiler, Ronald C.; Dewild, John F.; Gryziec, Joshua D.; Gusmeroli, Alessio; Hugelius, Gustaf; Jafarov, Elchin; Krabbenhoft, David P.; Liu, Lin; Herman‐Mercer, Nicole; et al.
Abstract: Changing climate in northern regions is causing permafrost to thaw with major implications for the global mercury (Hg) cycle. We estimated Hg in permafrost regions based on in situ measurements of sediment total mercury (STHg), soil organic carbon (SOC), and the Hg to carbon ratio (RHgC ) combined with maps of soil carbon. We measured a median STHg of 43 ± 30 ng Hg g soil −1 and a median RHgC of 1.6 ± 0.9 μg Hg g C −1, consistent with published results of STHg for tundra soils and 11, 000 measurements from 4, 926 temperate, nonpermafrost sites in North America and Eurasia. We estimate that the Northern Hemisphere permafrost regions contain 1, 656 ± 962 Gg Hg, of which 793 ± 461 Gg Hg is frozen in permafrost. Permafrost soils store nearly twice as much Hg as all other soils, the ocean, and the atmosphere combined, and this Hg is vulnerable to release as permafrost thaws over the next century. Existing estimates greatly underestimate Hg in permafrost soils, indicating a need to reevaluate the role of the Arctic regions in the global Hg cycle. Plain Language Summary: Researchers estimate the amount of natural mercury stored in perennially frozen soils (permafrost) in the Northern Hemisphere. Permafrost regions contain twice as much mercury as the rest of all soils, the atmosphere, and ocean combined. Key Points: Permafrost stores a significant amount of mercury Permafrost regions store twice as much mercury as all other soils, the ocean, and atmosphere combined Thawing permafrost in a warming climate may release mercury to the environment